BACAAN KEAGAMAAN AKTIVIS ROHIS: STUDI KASUS DI SMA NEGERI 3 DAN 4 KOTA MEDAN: RELIGIOUS READING MATERIALS OF ROHIS ACTIVISTS A CASE STUDY IN STATE SENIOR HIGH SCHOOLS 3 AND 4 IN MEDAN, NORTH SUMATERA - Zulkarnain Yani (Balai Penelitian dan Pengembangan Agama Jakarta, 2014)
This article presents the results of a case study on Senior High School Rohis activists’ reception of religious reading materials. Rohis (Rohani Islam) is one of the extra-curricular activities provided in most senior high schools. The case study was intended as policy research and conducted in Senior High School 3 and 4 in the City of Medan, North Sumatera. The author found that Rohis activists tend to be fond of popular religious reading materials which they are easy to understand. They also tend to overlook or have no knowledge on the authors (including their intellectual and life backgrounds) of the religious reading materials as well as the sources used as reference in those materials. Key Words: Rohis, religious reading materials, reception, Senior High School (SMA). Tulisan ini menyajikan hasil studi kasus terhadap resepsi aktivis Rohani Islam (Rohis) terhadap bahan bacaan keagamaan. Rohis adalah salah satu aktivitas ekstra-kurikuler yang banyak dilakukan di Sekolah Menengah Atas (SMA). Studi kasus ini dilakukan sebagai penelitian kebijakan di SMA 3 dan 4 di Kota Medan, Sumatera Utara. Hasil penelitian ini menunjukkan bahwa, para aktivis Rohis lebih menyukai bacaan keagamaan yang mudah dipahami. Mereka juga cenderung tidak memiliki pengetahuan akan penulis bahan bacaan tersebut (termasuk latar belakang intelektual dan kehidupannya), juga tidak mengetahui sumber-sumber yang digunakan sebagai referensi dalam bacaan tersebut. Kata Kunci: Rohis, bacaan keagamaan, resepsi, SMA.